1996
DOI: 10.1007/bf02425495
|View full text |Cite
|
Sign up to set email alerts
|

The validity and reliability of a test of lower body musculotendinous stiffness

Abstract: The aim of this study was to investigate the validity and reliability of an in vivo test of lower body musculotendinous stiffness. Male subjects (n = 23) with at least 12 months of weight training experience performed a series of quasi-static muscular actions in a supine leg press position during which a brief perturbation was applied. The resulting damped oscillations enabled each subject's maximal musculotendinous stiffness for the lower body musculature to be estimated. To assess the individual's capacity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
96
2
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(112 citation statements)
references
References 34 publications
8
96
2
6
Order By: Relevance
“…These results support the potentiation by SSC in previous studies that examined the movements of lower limbs (Asmussen and Bonde-Petersen, 1974;Bosco and Komi, 1979;Zushi and Takamatsu, 1995;Walshe et al, 1996) and upper limbs (Takamatsu et al, 1991;Wilson et al, 1992Wilson et al, , 1994Elliott et al, 1999). Asmussen and Bonde-Petersen (1974) reported that mechanical energy is conserved in a muscular elastic element during countermovement and it is reused in active work, and energy is hardly conserved in the muscle in a movement by which power is exerted from the state of the rest.…”
Section: Comparison Of Muscle Power Parameters In the Three Preliminasupporting
confidence: 90%
See 2 more Smart Citations
“…These results support the potentiation by SSC in previous studies that examined the movements of lower limbs (Asmussen and Bonde-Petersen, 1974;Bosco and Komi, 1979;Zushi and Takamatsu, 1995;Walshe et al, 1996) and upper limbs (Takamatsu et al, 1991;Wilson et al, 1992Wilson et al, , 1994Elliott et al, 1999). Asmussen and Bonde-Petersen (1974) reported that mechanical energy is conserved in a muscular elastic element during countermovement and it is reused in active work, and energy is hardly conserved in the muscle in a movement by which power is exerted from the state of the rest.…”
Section: Comparison Of Muscle Power Parameters In the Three Preliminasupporting
confidence: 90%
“…Studies on SSC were started by Cavagna et al (1965), and were conducted chiefly by Asmussen et al (1974), Walshe et al (1996) and Bosco and Komi (1979) using running or jumping. Although studies on SSC of the upper limbs have been conducted using elbow flexion (Takamatsu et al, 1991) or bench pressing (Wilson et al, 1991;Newton et al, 1996), there are very few such studies as compared with those for lower limbs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stiffness is calculated as change in joint moment divided by angular displacement (similar to joint stiffness) and related to the isometric torque of the preceding 20 ms with the stiffness-torque relationship considered an index of MTU stiffness. Reliability is established for both methods (Lambertz et al, 2008;McLachlan et al, 2006;Murphy, 2003) with construct validity established for the oscillation technique (Walshe et al, 1996). Neither method provides a measure of the stiffness of the tendon itself however, as measurement of that requires measurement of tendon elongation and tendon force.…”
Section: Introductionmentioning
confidence: 99%
“…7 The stretch shortening cycle (SSC) is highly utilized in many sports and sporting activities in which reactive ability is necessary. Furthermore, the more efficient the SSC, the better the rates of force development (RFD), 8 which itself is an important determinant of athletic performance.…”
Section: Introductionmentioning
confidence: 99%